Fecal Clostridium symbiosum for Noninvasive Detection of Early and Advanced Colorectal Cancer: Test and Validation Studies - Xie, Yuan-Hong; Gao, Qin-Yan; Cai, Guo-Xiang; Sun, Xiao-Ming; Zou, Tian-Hui; Chen, Hui-Min; Yu, Si-Yi; Qiu, Yi-Wen; Gu, Wei-Qi; Chen, Xiao-Yu; Cui, Yun; Sun, Danfeng; et al. (EBioMedicine, 2017)
Current non-invasive early detection of colorectal cancer (CRC) requires improvement. We aimed to identified a fecal Clostridium symbiosum-based biomarker for early and advanced colorectal cancer detection. In the test stage, the relative abundance of Clostridium symbiosum (C. symbiosum) was measured by qPCR in 781 cases including 242 controls, 212 colorectal adenoma (CRA) patients, 109 early CRC (tumor restricted to the submucosa) patients, 218 advanced CRC patients. The prediction accuracy was compared to Fusobacterium nucleatum (F. nucleatum), fecal immunochemical test (FIT) and CEA (carcinoembryonic antigen) and validated in an independent cohort of 256 subjects. Current status of the trial:ongoing/still enrolling. Primary endpoint:June, 2017 (Clinicaltrials.gov Identifier NCT02845973). Significant stepwise increase of C. symbiosum abundance was found in CRA, early CRC and advanced CRC (P<0.01). C. symbiosum outperformed all the other markers in early CRC prediction performance. The combination of C. symbiosum and FIT achieved better performance (0.803 for test cohort and 0.707 for validation cohort). For overall discrimination of CRCs, the combination of all above markers achieved the performance of 0.876. Fecal C. symbiosum is a promising biomarker for early and noninvasive detection of colorectal cancer, being more effective than F. nucleatum, FIT and CEA. Combining C. symbiosum and FIT or CEA may improve the diagnosis power. •The fecal abundance of Clostridium symbiosum was found increased in patients with colorectal neoplasia and it may serve as a potiential biomarker in non-invasive early differentiation of colorectal cancer from healthy controls.•The fecal abundance of Clostridium symbiosum was even more sensitive and efficient in diagnosis of both early and advanced colorectal cancer than reported markers like fecal immunochemical test, carcinoembryonic antigen and the abundance of Fusobacterium nucleatum.•Combining the abundance of Clostridium symbiosum and the other markers above may further enhance its predictive performance.